2020
DOI: 10.1002/ccd.29403
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early hospital discharge on clinical outcomes after transcatheter aortic valve implantation

Abstract: Aims Early discharge after transcatheter aortic valve implantation (TAVI) may potentially impact post‐procedural safety of the patient. The study aim was to compare safety of TAVI in patients planned for fast track hospital stay with patients planned for standard hospital stay. Methods and results All‐comers patients undergoing transfemoral TAVI between 2011 and 2017 were allocated to two matched groups depending whether the procedure was performed before or after transition from standard to fast track course.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…This may affect the outcome in two ways. The slower recovery of the surgical group may predispose to prolonged immobilization and increased infections rates [15,16], which are all known concerns in these frail surgical candidates. Indeed, lymphoceles and paresthesia complications are quite more common when a surgical femoral isolation is performed [17].…”
Section: Discussionmentioning
confidence: 99%
“…This may affect the outcome in two ways. The slower recovery of the surgical group may predispose to prolonged immobilization and increased infections rates [15,16], which are all known concerns in these frail surgical candidates. Indeed, lymphoceles and paresthesia complications are quite more common when a surgical femoral isolation is performed [17].…”
Section: Discussionmentioning
confidence: 99%
“…These improved outcomes were also associated with reduced in-hospital stay, with the median time from procedure to discharge falling from 130 h (2013) to 64 h (2016) ( 20 ). An all-corners patients’ retrospective analysis has shown that a fast-track median length of post-TAVI in-hospital stay of 3-days compared to a standard 6-day in-hospital stay did not have any difference in all-cause mortality (1.3 vs. 1.9%), rate of rehospitalization after discharge (2.09 per patient-year vs. 2.09 per patient-year) and rate of permanent pacemaker implantation (PPI) in pacemaker naive patients at 90 days (15.8 vs. 21.9%) ( 21 ). In addition, two prospective studies the 3M-TAVR and FAST-TAVI have shown that next-day discharge is safe in judiciously selected patients who undergo uncomplicated transfemoral TAVI ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 97%
“…Vascular closure devices (VCD) provide reliable access site control and allow for rapid mobilisation after procedures. These improvements have allowed for an increasing possibility of same-day discharge (SDD) after catheter-based interventions (13)(14)(15)(16)(17)(18)). An extensive review and summary discussing the feasibility of SDD after numerous transcatheter procedures was published by Asbeutah et al (18).…”
Section: Introductionmentioning
confidence: 99%